A splitting type algorithm for numerical solution of PDEs of fractional order - Abrashina‐Zhadaeva, Natali; Romanova, N. (Mathematical Modelling and Analysis, 2007)
Fractional order diffusion equations are generalizations of classical diffusion equations, treating super‐diffusive flow processes. In this paper, we examine a splitting type numerical methods to solve a class of two‐dimensional initial‐boundary value fractional diffusive equations. Stability, consistency and convergence of the methods are investigated. It is shown that both schemes are unconditionally stable. A numerical example is presented. First Published Online: 14 Oct 2010